Over-expression of CcMYB24, encoding a R2R3-MYB transcription factor from a high-leaf-number mutant of Cymbidium, increases the number of leaves in Arabidopsis - Li, Gengyun; Cheng, Longjie; Li, Zhilin; Zhao, Yiran; Wang, Yuying (PeerJ, 2023)
Ornamental foliage plants have long been cultivated for their attractive leaves. Variation in leaf traits of ornamental foliage plants is one of the goals in breeding. MYB transcription factors regulate many aspects of leaf development, and thus influence morphological traits of leaves. However, little is known about the function of MYB transcription factors in leaf development of Cymbidium, one of the most economically important ornamental plants in the world. In the present study, a MYB transcription factor, CcMYB24, was identified and the corresponding gene cloned from a new orchid mutant, TRIR-2, which produces more leaves than control plants. The CcMYB24 showed a higher expression level in ‘TRIR-2’ than in control plants, and the protein was located in the nucleus. The sequence of CcMYB24 showed a high similarity with RAX2-like genes which belong to the R2R3-MYB gene family in other Cymbidium plants. Overexpression of CcMYB24 resulted in a phenotype with an increased number of leaves, elevated chlorophyll content, and decreased contents of carotenoids and flavonoids in Arabidopsis. These results provide functional evidence for the role of CcMYB24 in promoting the production of leaves in ‘TRIR-2’. Understanding the role of CcMYB24 in Cymbidium will be beneficial for the molecular breeding of ornamental foliage plants.
Keywords: CcMYB24; Cymbidium; Leaf number; Ornamental foliage plants; MYB transcription factor; Mutant